The catalytic mechanism of cyclic GMP‐AMP synthase (cGAS) and implications for innate immunity and inhibition. (25th October 2017) - Hall, Justin; Ralph, Erik C.; Shanker, Suman; Wang, Hong; Byrnes, Laura J.; Horst, Reto; Wong, Jimson; Brault, Amy; Dumlao, Darren; Smith, James F.; Dakin, Leslie A.; Schmitt, Daniel C.; et al.
Abstract: Cyclic GMP‐AMP synthase (cGAS) is activated by ds‐DNA binding to produce the secondary messenger 2′, 3′‐cGAMP. cGAS is an important control point in the innate immune response; dysregulation of the cGAS pathway is linked to autoimmune diseases while targeted stimulation may be of benefit in immunoncology. We report here the structure of cGAS with dinucleotides and small molecule inhibitors, and kinetic studies of the cGAS mechanism. Our structural work supports the understanding of how ds‐DNA activates cGAS, suggesting a site for small molecule binders that may cause cGAS activation at physiological ATP concentrations, and an apparent hotspot for inhibitor binding. Mechanistic studies of cGAS provide the first kinetic constants for 2′, 3′‐cGAMP formation, and interestingly, describe a catalytic mechanism where 2′, 3′‐cGAMP may be a minor product of cGAS compared with linear nucleotides. Abstract : PDB Code(s):5VDQ, ;5VDO, ;5VDP, ;5VDT, ;5VDR, ;5VDS, ;5VDW, ;5VDU, ;5VDV